2012
DOI: 10.1074/jbc.m111.326900
|View full text |Cite
|
Sign up to set email alerts
|

Neural Crest Deletion of Dlx3 Leads to Major Dentin Defects through Down-regulation of Dspp

Abstract: Background: Mutations of DLX3 in humans lead to tooth defects, but normal Dlx3 function in tooth is unknown. Results: Mice lacking Dlx3 in the dental mesenchyme exhibit major dentin defects, and Dspp is a direct target of Dlx3 in odontoblasts. Conclusion: Dspp, a major component of dentin matrix, is directly regulated by Dlx3 in odontoblasts. Significance: Dspp is the first direct target of Dlx3 identified in odontoblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 53 publications
5
72
0
Order By: Relevance
“…We observed similar inhibitory effects of miR-665 overexpression on the expression of Mmp20 and Klk4 (Fig. 3D), already reported as downstream targets of Dlx3 essential for tooth matrix formation (30). Similar inhibition of dentinogenesis was also observed on day 7 of odontoblast differentiation in miR-665-overexpressing cells.…”
Section: Discovery Of Mir-665supporting
confidence: 87%
See 3 more Smart Citations
“…We observed similar inhibitory effects of miR-665 overexpression on the expression of Mmp20 and Klk4 (Fig. 3D), already reported as downstream targets of Dlx3 essential for tooth matrix formation (30). Similar inhibition of dentinogenesis was also observed on day 7 of odontoblast differentiation in miR-665-overexpressing cells.…”
Section: Discovery Of Mir-665supporting
confidence: 87%
“…Studies from several research groups have revealed that homeodomain gene Dlx3 (Online Mendelian Inheritance in Man [OMIM] entry 600525) is a highly critical regulator of craniofacial and postnatal skeletal development (28)(29)(30)(31)(32)(33)(34). Mutations in DLX3 in humans have been associated with tricho-dento-osseous syndrome (TDO; OMIM 190320) and amelogenesis imperfecta with taurodontism (AIHHT; OMIM 104510), both of which are conditions characterized by abnormalities in tooth formation (35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we tested the expressions of three molecular markers: a homeodomain-containing transcription factor, Dlx3, and two odontoblast differentiation markers, Col1a1 and biglycan. Dlx3 has been shown to regulate dentinogenesis through directly regulating Dspp expression (33). We found that Dlx3 was expressed predominantly in the odontoblasts of WT (Fig.…”
Section: Transgenic Expression Of Dspp Rescued the Dentin Mineralizatmentioning
confidence: 67%